Application of transition metal Fe modified Pt-based catalyst in preparation of 1, 2-pentanediol through selective hydrogenolysis of furfural or furfuryl alcohol

By using a supported Pt-Fe catalyst modified by transition metal Fe, the efficient conversion of furfural or furfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfur

CN119684083APending Publication Date: 2025-03-25DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311253652.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing catalysts have problems such as cumbersome reaction process, harsh conditions, low yield and poor catalyst stability in the selective conversion of furfural or furfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurf

Method used

The supported Pt-Fe catalyst modified with transition metal Fe is used to achieve efficient hydrogenolysis of furfural or furfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfur

Benefits of technology

The selectivity and yield of 1,2-pentanediol is significantly improved under mild conditions, and the catalyst is stable, which is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684083A_ABST
    Figure CN119684083A_ABST
Patent Text Reader

Abstract

The invention relates to application of a Pt-based catalyst modified by transition metal Fe in preparation of 1, 2-pentanediol through selective hydrogenolysis of furfural or furfuryl alcohol. According to the method, furfural or furfuryl alcohol is converted into pentanediol in one step under the action of a supported Pt-Fe catalyst by taking water as a medium. The catalyst takes a magnesium-containing composite oxide as a carrier, Pt as an active component and transition metal Fe as an auxiliary agent, wherein the carrier is a composite oxide of Mg and one or more than two of Zn, Ti, Mn, Al and Si. Under the optimal reaction condition, the selectivity of the 1, 2-pentanediol can be remarkably improved by adding a proper amount of auxiliary Fe, and the yield of the 1, 2-pentanediol can reach 75% or above. The method has the remarkable advantages of cheap and easily available raw materials, simplicity in operation, recyclability, simplicity and convenience in recovery and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to converting furfural or furfuryl alcohol into pentanediol in one step by using water as a medium and under the action of a supported Pt-Fe catalyst, wherein the yield of 1,2-pentanediol is not less than 75%. Background Art

[0002] 1,2-Pentanediol is a key raw material for the synthesis of the fungicide propiconazole, and is also increasingly used in skin care products as a moisturizer and solubilizer. 1,2-Pentanediol is mainly obtained in industry by converting the petroleum cracking product n-pentene. Due to economic reasons, the current bio-based route to produce 1,2-pentanediol from furfural has received increasing attention and research. The production of 1,2-pentanediol from the biomass platform compound furfural has significant advantages such as renewable raw materials, short reaction routes, and good technical and economic efficiency. However, the furfural molecule has both a C=O double bond and a C=C double bond, which is very active and easily generates other by-products. The current literature and patents on the selective hydrogenolysis of furfural are mainly as follows. Its activity and selectivity vary with the different carriers and active components.

[0003] In the literature (J.Am.Chem.Soc., 1931, 53(3), 1091-1095), CuCr2O was used as a catalyst to achieve the conversion of furfuryl alcohol to pentanediol at 175°C and 10MPa of hydrogen, with a yield of 40% for 1,2-pentanediol and 30% for 1,5-pentanediol. However, the use of Cr in the catalyst will pollute the environment and is harmful to the human body, with a risk of carcinogenesis, making it difficult to apply in industrial production.

[0004] In the literature (Catal. Today, 2018, 309(1), 195-201), Pd / MMK-T catalyst was used to obtain 66% of 1,2-pentanediol, without 1,5-pentanediol. However, the catalyst had poor stability and its activity decreased after the second cycle.

[0005] In the literature (Green Chem., 2012, 14(12), 3402-3409), noble metal catalysts such as Pt and Ru were used, but the yield of 1,2-pentanediol was low, many by-products such as tetrahydrofurfuryl alcohol were produced, and the selectivity of the catalyst for 1,2-pentanediol was low.

[0006] In patent CN104370702A, a Cu-based catalyst is used to hydrogenate furfuryl alcohol to generate 1,2-pentanediol. Although a non-precious metal catalyst is used, the conversion rate of furfuryl alcohol is low and the yield of 1,2-pentanediol is low.

[0007] In patent CN113318735A, MgTiO was synthesized by sol-gel method. x MgFeO x MgCeOx The reducible composite oxide support, after impregnation with Pt, obtained a higher total yield of 1,2-pentanediol and 1,5-pentanediol, but the yield of 1,2-pentanediol was lower.

[0008] Based on the above literature and patent reports, it can be seen that the use of existing precious metal and non-precious metal catalyst systems has many problems such as complicated reaction process, harsh reaction conditions, low yield of 1,2-pentanediol, and poor catalyst stability. Therefore, it is urgent to develop cheap and efficient catalysts to achieve the selective one-step conversion of furfural or furfuryl alcohol into 1,2-pentanediol. Summary of the invention

[0009] The present invention aims to provide an efficient Pt-Fe catalyst for hydrogenolysis of furfural or furfuryl alcohol to prepare 1,2-pentanediol. The catalyst can hydrogenolyze furfural or furfuryl alcohol to 1,2-pentanediol under mild conditions, the yield of 1,2-pentanediol is not less than 75%, and the catalyst has good stability.

[0010] To achieve the above object, the technical scheme adopted by the present invention is: in an intermittent stirred reactor or a continuous fixed bed, furfural or furfuryl alcohol is used as a raw material, water is used as a solvent, and under the action of a Pt-based catalyst modified with a transition metal Fe, the yield of 1,2-pentanediol is not less than 75%;

[0011] The composition of the catalyst is Pt-Fe / MgMO3, M is one or more of Zn, Ti, Mn, Al, Si, and the mass fraction of Mg content in the carrier MgMO3 is 15-60wt%, preferably 30-60wt%; the active component of the catalyst is Pt, and the loading amount of Pt is 0.1-10wt% of the carrier mass, preferably 0.4-4wt%; the catalyst auxiliary agent component is Fe, and the loading amount of Fe is 0.05-5wt% of the carrier mass, preferably 0.3-4wt%.

[0012] The carrier MgMO3 is prepared by a sol-gel method or a precipitation method.

[0013] The preparation process of the sol-gel method is as follows: weigh one or more of tetrabutyl titanate / zinc acetylacetonate / manganese acetylacetonate / aluminum sec-butylate / ethyl silicate and dissolve them in ethanol, stir them evenly to obtain an alcohol solution; weigh magnesium nitrate and dissolve it in ultrapure water to obtain an aqueous solution; the mass fraction of Mg in the carrier MgMO3 is 15-60wt%, preferably 30-60wt%. The alcohol solution and the aqueous solution are mixed under magnetic stirring, and white floccules appear. Nitric acid with a mass fraction of 30-80% (preferably 50-70%) is added to dissolve the precipitate to obtain a clear solution, and then citric acid (n 柠檬酸 :n 金属=1-4:1 (preferably 1.5-3:1)), glucose (concentration of 10-40 g / 100 mL (preferably 20-30 g / 100 mL)) and acrylamide monomer (n 丙烯酰胺 :n 金属 =5-15:1 (preferably 8-12:1)), after dissolving, add 10-28wt% (preferably 15-25wt%) of ammonia water to adjust the pH to 1-5 (preferably 2-4), heat in a water bath at 60-100°C (preferably 70-90°C) for 4-5h, dry the formed gel at 80-180°C (preferably 100-160°C) for 8-24h (preferably 10-20h), grind, place in a muffle furnace at 600-900°C (preferably 700-800°C) for calcination for 2-6h (preferably 3-5h) to obtain the carrier MgMO x ;

[0014] The preparation process of the precipitation method is as follows: weigh one or two of titanium sulfate / zinc sulfate / manganese sulfate / aluminum nitrate and dissolve them in ultrapure water; weigh magnesium sulfate heptahydrate and dissolve it in ultrapure water; the Mg content in the carrier MgMO3 is not less than 15%, preferably 15-60%, and the two salt solutions are mixed to obtain a clear solution a. Weigh sodium hydroxide and dissolve it in ultrapure water to obtain a sodium hydroxide solution with a mass fraction of 3-15wt% (preferably 5-10wt%). Under magnetic stirring, add the salt solution dropwise to the sodium hydroxide solution to form a uniform white suspension. The resulting suspension is placed in an oven at 60-120°C (preferably 80-100°C) for aging for 4-5h, then filtered, washed and dried; the dried sample is ground and placed in a muffle furnace at 600-900°C (preferably 700-800°C) for calcination for 2-6h (preferably 3-5h) to obtain the carrier MgMO x -P.

[0015] Next, the active component Pt and the auxiliary agent Fe are loaded on the carrier MgMO3 by an impregnation method, and the specific process is as follows: a) a precursor solution containing 0.001-0.1g Pt and a precursor solution containing 0.0005-0.05g Fe are added to a beaker, ultrapure water is added to make the total mass of the solution 0.54g, and mixed evenly to obtain a solution containing Pt and Fe; b) 1g of the carrier MgMO3 is added to the solution of step a) and stirred evenly, and the obtained mixture is allowed to stand for 8-18h (preferably 10-15h), and then dried in an oven at 80-120°C (preferably 100-120°C) for 10-15h (preferably 11-13h), and Pt-Fe / MgMO3-cal is obtained by calcining at 200-600°C (preferably 300-400°C) in a muffle furnace for 2-5h (preferably 3-4h); c) the Pt-Fe / MgMO3-cal obtained in step 3) is reduced in a hydrogen atmosphere for 0.5-3h (preferably 0.5-1.5h), and the reduction temperature is 100-600°C (preferably 300-400°C). After the reduction is completed, it is cooled to room temperature, and the hydrogen is switched to 1% by volume oxygen / nitrogen for passivation for 4-12h (preferably 4-6h) to obtain the transition metal Fe-modified Pt-based catalyst. The obtained catalyst is marked as Pt-Fe / MgMO3.

[0016] The precursor of Pt is one or more of platinum chloride, chloroplatinic acid, platinum nitrate, and platinum complexes (such as tetraamminedichloroplatinum, platinum acetylacetonate, bis(tri-tert-butylphosphine)platinum, dichloro(1,5-cyclooctadiene)platinum, etc.); the precursor of Fe is one or more of ferric nitrate, ferric acetate, and ferric chloride.

[0017] The catalyst is used in the selective hydrogenolysis reaction of furfural or furfural alcohol. The reaction raw material is furfural or furfural alcohol, the solvent is water, the mass concentration of furfural or furfural alcohol in water is 0.1-50%, preferably 1-30%; the hydrogen pressure is 0.1-10MPa, preferably 1-5MPa; the reaction temperature is 80-300°C, preferably 120-160°C; and the mass ratio of the catalyst to furfural or furfural alcohol is 0.1-5.

[0018] The catalyst of the present invention is a supported catalyst with Pt as an active component and Fe as a key auxiliary agent. The catalyst directly converts furfural or furfuryl alcohol into high value-added chemical 1,2-pentanediol under mild conditions, and has the significant advantages of easy raw material availability, high selectivity of target product, and short reaction process route. The addition of an appropriate amount of auxiliary agent Fe can significantly improve the selectivity of 1,2-pentanediol, and the yield of 1,2-pentanediol can reach more than 75%. The present invention has the significant advantages of cheap and easy raw materials, simple operation, recyclable use, and simple recovery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1The cyclic stability of the catalyst in the furfural hydrogenolysis reaction. DETAILED DESCRIPTION

[0020] The following examples will help to understand the present invention, but the protection scope of the present invention is not limited to these examples.

[0021] Example 1

[0022] 5 mmol of tetrabutyl titanate was weighed and dissolved in 25 mL of ethanol, and stirred evenly to obtain an alcohol solution; 25 mL of 0.2 mol / L magnesium nitrate solution was weighed to obtain an aqueous solution; the alcohol solution and the aqueous solution were mixed under magnetic stirring, and white floccules appeared. 2 mL of nitric acid with a mass fraction of 68% was added to dissolve the precipitate to obtain a clear solution, and then 15 mmol of citric acid, 10 g of glucose and 0.09 mol of acrylamide monomer were added to the mixed solution. After dissolution, 25 wt% ammonia water was added to adjust the pH to 3, and the mixture was heated in a water bath at 80°C for 5 h. The formed gel was dried at 150°C for 12 h and then ground, and placed in a muffle furnace for calcination at 700°C for 4 h to obtain a carrier MgTiO x (2≤x≤3).

[0023] Weigh 2 mL of chloroplatinic acid aqueous solution and 2 mL of ferric nitrate aqueous solution, mix them, and add 1 g of the synthesized carrier MgTiO x , the mass loading amount of metal Pt (relative to the mass of the carrier in the catalyst, the same below) is 1%, the mass loading amount of metal Fe (relative to the mass of the carrier in the catalyst, the same below) is 0.8%, after being stirred evenly, impregnated for 12 hours, dried at 100°C for 12 hours, calcined at 300°C in an air atmosphere for 3 hours, and the calcined catalyst was reduced at 300°C in a hydrogen atmosphere for 1 hour. After the reduction is completed, it is cooled to room temperature, and the hydrogen is switched to 1% by volume oxygen / nitrogen to purge passivation for 4 hours to obtain the catalyst 1Pt0.8Fe / MgTiO x An intermittent stirring reactor was selected, the mass concentration of furfural aqueous solution was 2%, the amount of catalyst was 0.1 g, the reaction temperature was 140°C, the reaction pressure was 1 MPa, and the reaction time was 10 h. The catalytic results of the catalyst are shown in Table 1.

[0024] Example 2

[0025] Weigh 5mmol titanium sulfate and dissolve it in 25mL ultrapure water; weigh 5mmol magnesium sulfate heptahydrate and dissolve it in 25mL ultrapure water; mix the two salt solutions to obtain a clear solution a. Weigh 0.12mol sodium hydroxide and dissolve it in 50mL ultrapure water. Under magnetic stirring, add the salt solution dropwise to the sodium hydroxide solution to form a uniform white suspension. The resulting suspension is aged in an oven at 80℃ for 4h, then filtered, washed and dried; the dried sample is ground and calcined in a muffle furnace at 700℃ for 4h to obtain the carrier MgTiO x -P.

[0026] Weigh 2 mL of chloroplatinic acid aqueous solution and 2 mL of ferric nitrate aqueous solution, mix them, and add 1 g of the synthesized carrier MgTiO x -P, the mass loading amount of metal Pt (relative to the mass of the carrier in the catalyst, the same below) is 1%, the mass loading amount of metal Fe (relative to the mass of the carrier in the catalyst, the same below) is 0.8%, after being stirred evenly, impregnated for 12 hours, dried at 100°C for 12 hours, calcined at 300°C in an air atmosphere for 3 hours, and the calcined catalyst was reduced at 300°C in a hydrogen atmosphere for 1 hour. After the reduction, it was cooled to room temperature, and the hydrogen was switched to 1% by volume oxygen / nitrogen to purge and passivate for 4 hours to obtain the catalyst 1Pt0.8Fe / MgTiO x -P. An intermittent stirred reactor was selected, the mass concentration of furfural aqueous solution was 2%, the amount of catalyst was 0.1 g, the reaction temperature was 140°C, the reaction pressure was 1 MPa, and the reaction time was 10 h. The catalytic results of the catalyst are shown in Table 1.

[0027] Example 3

[0028] 5mmol of zinc acetylacetonate, manganese acetylacetonate, aluminum sec-butoxide, and ethyl silicate were weighed and dissolved in 25mL of ethanol, and stirred evenly to obtain an alcohol solution; 25mL of 0.2mol / L magnesium nitrate solution was weighed to obtain an aqueous solution; the alcohol solution and the aqueous solution were mixed under magnetic stirring, and white floccules appeared. 2mL of 68% nitric acid was added to dissolve the precipitate to obtain a clear solution, and then 15mmol of citric acid, 10g of glucose, and 0.09mol of acrylamide monomer were added to the mixed solution. After dissolution, 25wt% ammonia water was added to adjust the pH to 3, and the mixture was heated in a water bath at 80℃ for 5h. The formed gel was dried at 150℃ for 12h and then ground, and placed in a muffle furnace for calcination at 700℃ for 4h to obtain carriers MgZnO and MgZnO. x (1.5≤x≤2.2),MgMnO x (2≤x≤3),MgAlO x (2≤x≤3),MgSiO x (2≤x≤3).

[0029] Weigh 2 mL of chloroplatinic acid aqueous solution and 2 mL of ferric nitrate aqueous solution, mix them, add 1 g of the above-synthesized carrier, make the mass loading of metal Pt (relative to the mass of the carrier in the catalyst, the same below) 1%, the mass loading of metal Fe (relative to the mass of the carrier in the catalyst, the same below) 0.8%, stir evenly and soak for 12 h, dry at 100 ° C for 12 h, calcine at 300 ° C for 3 h in air atmosphere, reduce the calcined catalyst at 300 ° C for 1 h in hydrogen atmosphere, cool to room temperature after reduction, switch hydrogen to 1% by volume, and purge passivation for 4 h to obtain the catalyst 1Pt0.8Fe / MgZnO x, 1Pt0.8Fe / MgMnO x ,1Pt0.8Fe / MgAlO x , 1Pt0.8Fe / MgSiO x An intermittent stirring reactor was selected, the mass concentration of furfural aqueous solution was 2%, the amount of catalyst was 0.1 g, the reaction temperature was 140°C, the reaction pressure was 1 MPa, and the reaction time was 10 h. The catalytic results of the catalyst are shown in Table 1.

[0030] Example 4

[0031] 2.5 mmol of tetrabutyl titanate and 2.5 mmol of ethyl silicate were weighed and dissolved in 25 mL of ethanol, and stirred evenly to obtain an alcohol solution; 25 mL of 0.2 mol / L magnesium nitrate solution was weighed to obtain an aqueous solution; the alcohol solution and the aqueous solution were mixed under magnetic stirring, and white floccules appeared. 2 mL of nitric acid with a mass fraction of 68% was added to dissolve the precipitate to obtain a clear solution, and then 15 mmol of citric acid, 10 g of glucose and 0.09 mol of acrylamide monomer were added to the mixed solution. After dissolution, 25 wt% of ammonia water was added to adjust the pH to 3, and the mixture was heated in a water bath at 80°C for 5 h. The formed gel was dried at 150°C for 12 h and then ground, and placed in a muffle furnace for calcination at 700°C for 4 h to obtain a carrier MgTiSiO x (3≤x≤5).

[0032] Weigh 2 mL of chloroplatinic acid aqueous solution and 2 mL of ferric nitrate aqueous solution, mix them, and add 1 g of the synthesized carrier MgTiSiO x , the mass loading amount of metal Pt (relative to the mass of the carrier in the catalyst, the same below) is 1%, the mass loading amount of metal Fe (relative to the mass of the carrier in the catalyst, the same below) is 0.8%, after being stirred evenly, impregnated for 12 hours, dried at 100°C for 12 hours, calcined at 300°C in an air atmosphere for 3 hours, and the calcined catalyst was reduced at 300°C in a hydrogen atmosphere for 1 hour. After the reduction is completed, it is cooled to room temperature, and the hydrogen is switched to 1% by volume oxygen / nitrogen to purge passivation for 4 hours to obtain the catalyst 1Pt0.8Fe / MgTiSiO x An intermittent stirring reactor was selected, the mass concentration of furfural aqueous solution was 2%, the amount of catalyst was 0.1 g, the reaction temperature was 140°C, the reaction pressure was 1 MPa, and the reaction time was 10 h. The catalytic results of the catalyst are shown in Table 1.

[0033] Example 5

[0034] The furfural aqueous solution with a mass concentration of 2% was replaced with a furfuryl alcohol aqueous solution with a mass concentration of 2%, and other conditions and processes were the same as those in Example 1. The catalytic results of the catalyst are shown in Table 1.

[0035] Comparative Example 1

[0036] MgTiOx The preparation operation is the same as in Example 1.

[0037] Weigh 2 mL of chloroplatinic acid aqueous solution and add 1 g of the synthesized carrier MgTiO x , the mass loading amount of metal Pt (relative to the mass of the carrier in the catalyst, the same below) is 1%, and the mixture is stirred evenly and impregnated for 12 hours, dried at 100°C for 12 hours, and calcined at 300°C for 3 hours in an air atmosphere. After calcination, the catalyst is reduced at 300°C for 1 hour in a hydrogen atmosphere, cooled to room temperature after the reduction, and the hydrogen is switched to 1% by volume oxygen / nitrogen for passivation for 4 hours to obtain the catalyst 1Pt / MgTiO x An intermittent stirring reactor was selected, the mass concentration of furfural aqueous solution was 2%, the amount of catalyst was 0.1 g, the reaction temperature was 140°C, the reaction pressure was 1 MPa, and the reaction time was 10 h. The catalytic results of the catalyst are shown in Table 1.

[0038] Comparative Example 2

[0039] MgTiO x The preparation operation is the same as in Example 1.

[0040] Weigh 2 mL of chloroplatinic acid aqueous solution and 2 mL of cobalt nitrate aqueous solution, and add 1 g of the synthesized carrier MgTiO x , the mass loading amount of metal Pt (relative to the mass of the carrier in the catalyst, the same below) is 1%, the mass loading amount of metal Co (relative to the mass of the carrier in the catalyst, the same below) is 0.8%, after being stirred evenly, impregnated for 12 hours, dried at 100°C for 12 hours, calcined at 300°C in an air atmosphere for 3 hours, and the calcined catalyst was reduced at 300°C in a hydrogen atmosphere for 1 hour. After the reduction is completed, it is cooled to room temperature, and the hydrogen is switched to 1% by volume oxygen / nitrogen to purge passivation for 4 hours to obtain the catalyst 1Pt0.8Co / MgTiO x An intermittent stirring reactor was selected, the mass concentration of furfural aqueous solution was 2%, the amount of catalyst was 0.1 g, the reaction temperature was 140°C, the reaction pressure was 1 MPa, and the reaction time was 10 h. The catalytic results of the catalyst are shown in Table 1.

[0041] Comparative Example 3

[0042] MgTiO x The preparation operation is the same as in Example 1.

[0043] Weigh 2 mL of chloroplatinic acid aqueous solution and 2 mL of nickel nitrate aqueous solution, and add 1 g of the synthesized carrier MgTiO x, the mass loading amount of metal Pt (relative to the mass of the carrier in the catalyst, the same below) is 1%, the mass loading amount of metal Ni (relative to the mass of the carrier in the catalyst, the same below) is 0.8%, after being stirred evenly, impregnated for 12 hours, dried at 100°C for 12 hours, calcined at 300°C in an air atmosphere for 3 hours, and the calcined catalyst was reduced at 300°C in a hydrogen atmosphere for 1 hour. After the reduction, it was cooled to room temperature, and the hydrogen was switched to 1% by volume oxygen / nitrogen to purge passivation for 4 hours to obtain the catalyst 1Pt0.8Ni / MgTiO x An intermittent stirring reactor was selected, the mass concentration of furfural aqueous solution was 2%, the amount of catalyst was 0.1 g, the reaction temperature was 140°C, the reaction pressure was 1 MPa, and the reaction time was 10 h. The catalytic results of the catalyst are shown in Table 1.

[0044] Comparative Example 4

[0045] MgTiO x The preparation operation is the same as in Example 1.

[0046] Weigh 2 mL of chloroplatinic acid aqueous solution and 2 mL of copper nitrate aqueous solution, and add 1 g of the synthesized carrier MgTiO x , the mass loading amount of metal Pt (relative to the mass of the carrier in the catalyst, the same below) is 1%, the mass loading amount of metal Cu (relative to the mass of the carrier in the catalyst, the same below) is 0.8%, after being stirred evenly, impregnated for 12 hours, dried at 100°C for 12 hours, calcined at 300°C in an air atmosphere for 3 hours, and the calcined catalyst was reduced at 300°C in a hydrogen atmosphere for 1 hour. After the reduction, it was cooled to room temperature, and the hydrogen was switched to 1% by volume oxygen / nitrogen purging passivation for 4 hours to obtain the catalyst 1Pt0.8Cu / MgTiO x An intermittent stirring reactor was selected, the mass concentration of furfural aqueous solution was 2%, the amount of catalyst was 0.1 g, the reaction temperature was 140°C, the reaction pressure was 1 MPa, and the reaction time was 10 h. The catalytic results of the catalyst are shown in Table 1.

[0047] Comparative Example 5

[0048] MgTiO x The preparation operation is the same as in Example 1.

[0049] Weigh 2 mL of cobalt nitrate aqueous solution and 2 mL of ferric nitrate aqueous solution, mix them, and add 1 g of the synthesized carrier MgTiO x, the mass loading amount of metal Co (relative to the mass of the carrier in the catalyst, the same below) is 1%, the mass loading amount of metal Fe (relative to the mass of the carrier in the catalyst, the same below) is 0.8%, after being stirred evenly, impregnated for 12 hours, dried at 100°C for 12 hours, calcined at 300°C in air atmosphere for 3 hours, and the calcined catalyst was reduced at 300°C in hydrogen atmosphere for 1 hour. After the reduction, it was cooled to room temperature, and the hydrogen was switched to 1% by volume oxygen / nitrogen purging passivation for 4 hours to obtain the catalyst 1Co0.8Fe / MgTiO x An intermittent stirring reactor was selected, the mass concentration of furfural aqueous solution was 2%, the amount of catalyst was 0.1 g, the reaction temperature was 140°C, the reaction pressure was 1 MPa, and the reaction time was 10 h. The catalytic results of the catalyst are shown in Table 1.

[0050] Comparative Example 6

[0051] MgTiO x The preparation operation is the same as in Example 1.

[0052] Weigh 2 mL of nickel nitrate aqueous solution and 2 mL of iron nitrate aqueous solution, mix them, and add 1 g of the synthesized carrier MgTiO x The mass loading amount of metal Ni (relative to the mass of the carrier in the catalyst, the same below) is 1%, the mass loading amount of metal Fe (relative to the mass of the carrier in the catalyst, the same below) is 0.8%, and the mixture is stirred evenly and impregnated for 12 hours, dried at 100°C for 12 hours, and calcined at 300°C for 3 hours in an air atmosphere. After calcination, the catalyst is reduced at 300°C for 1 hour in a hydrogen atmosphere, cooled to room temperature after the reduction, and switched to hydrogen with a volume content of 1% oxygen / nitrogen for passivation for 4 hours to obtain the catalyst 1Ni0.8Fe / MgTiO x An intermittent stirring reactor was selected, the mass concentration of furfural aqueous solution was 2%, the amount of catalyst was 0.1 g, the reaction temperature was 140°C, the reaction pressure was 1 MPa, and the reaction time was 10 h. The catalytic results of the catalyst are shown in Table 1.

[0053] Comparative Example 7

[0054] MgTiO x The preparation operation is the same as in Example 1.

[0055] Weigh 2 mL of copper nitrate aqueous solution and 2 mL of iron nitrate aqueous solution, mix them, and add 1 g of the synthesized carrier MgTiO xThe mass loading of metal Cu (relative to the mass of the carrier in the catalyst, the same below) was 1%, and the mass loading of metal Fe (relative to the mass of the carrier in the catalyst, the same below) was 0.8%. After being stirred evenly, the mixture was impregnated for 12 h, dried at 100 ° C for 12 h, and calcined at 300 ° C for 3 h in an air atmosphere. After calcination, the catalyst was reduced at 300 ° C for 1 h in a hydrogen atmosphere. After the reduction was completed, the catalyst was cooled to room temperature, and the hydrogen was switched to 1% by volume. Oxygen / nitrogen was purged and passivated for 4 h to obtain the catalyst 1Cu0.8Fe / MgTiO x An intermittent stirring reactor was selected, the mass concentration of furfural aqueous solution was 2%, the amount of catalyst was 0.1 g, the reaction temperature was 140°C, the reaction pressure was 1 MPa, and the reaction time was 10 h. The catalytic results of the catalyst are shown in Table 1.

[0056] Comparative Example 8

[0057] MgTiO x The preparation operation is the same as in Example 1.

[0058] Weigh 2 mL of ruthenium trichloride aqueous solution and 2 mL of ferric nitrate aqueous solution, mix them, and add 1 g of the synthesized carrier MgTiO x The mass loading amount of metal Ru (relative to the mass of the support in the catalyst, the same below) was 1%, and the mass loading amount of metal Fe (relative to the mass of the support in the catalyst, the same below) was 0.8%. After being stirred evenly, the mixture was impregnated for 12 h, dried at 100 ° C for 12 h, and calcined at 300 ° C for 3 h in an air atmosphere. After calcination, the catalyst was reduced at 300 ° C for 1 h in a hydrogen atmosphere. After the reduction was completed, the catalyst was cooled to room temperature, and the hydrogen was switched to 1% by volume. The oxygen / nitrogen was purged and passivated for 4 h to obtain the catalyst 1Ru0.8Fe / MgTiO x An intermittent stirring reactor was selected, the mass concentration of furfural aqueous solution was 2%, the amount of catalyst was 0.1 g, the reaction temperature was 140°C, the reaction pressure was 1 MPa, and the reaction time was 10 h. The catalytic results of the catalyst are shown in Table 1.

[0059] Comparative Example 9

[0060] MgTiO x The preparation operation is the same as in Example 1.

[0061] Weigh 2 mL of palladium nitrate aqueous solution and 2 mL of ferric nitrate aqueous solution, mix them, and add 1 g of the synthesized carrier MgTiO x, the mass loading amount of metal Pd (relative to the mass of the carrier in the catalyst, the same below) is 1%, the mass loading amount of metal Fe (relative to the mass of the carrier in the catalyst, the same below) is 0.8%, after being stirred evenly, impregnated for 12 hours, dried at 100°C for 12 hours, calcined at 300°C in an air atmosphere for 3 hours, and the calcined catalyst was reduced at 300°C in a hydrogen atmosphere for 1 hour. After the reduction is completed, it is cooled to room temperature, and the hydrogen is switched to 1% by volume oxygen / nitrogen to purge passivation for 4 hours to obtain the catalyst 1Pd0.8Fe / MgTiO x An intermittent stirring reactor was selected, the mass concentration of furfural aqueous solution was 2%, the amount of catalyst was 0.1 g, the reaction temperature was 140°C, the reaction pressure was 1 MPa, and the reaction time was 10 h. The catalytic results of the catalyst are shown in Table 1.

[0062] Comparative Example 10

[0063] MgTiO x The preparation operation is the same as in Example 1.

[0064] Weigh 2 mL of rhodium chloride aqueous solution and 2 mL of ferric nitrate aqueous solution, mix them, and add 1 g of the synthesized carrier MgTiO x The mass loading amount of metal Rh (relative to the mass of the carrier in the catalyst, the same below) was 1%, and the mass loading amount of metal Fe (relative to the mass of the carrier in the catalyst, the same below) was 0.8%. After being stirred evenly, the mixture was impregnated for 12 h, dried at 100 ° C for 12 h, and calcined at 300 ° C for 3 h in an air atmosphere. After calcination, the catalyst was reduced at 300 ° C for 1 h in a hydrogen atmosphere. After the reduction was completed, the catalyst was cooled to room temperature, and the hydrogen was switched to 1% by volume. Oxygen / nitrogen was purged and passivated for 4 h to obtain the catalyst 1Rh0.8Fe / MgTiO x An intermittent stirring reactor was selected, the mass concentration of furfural aqueous solution was 2%, the amount of catalyst was 0.1 g, the reaction temperature was 140°C, the reaction pressure was 1 MPa, and the reaction time was 10 h. The catalytic results of the catalyst are shown in Table 1.

[0065] Table 1 Catalytic results of different catalysts

[0066]

[0067] *Others include small amounts of tetrahydrofurfuryl alcohol, cyclopentanone or 1,5-pentanediol, etc., and the overall material is conserved.

[0068] From the above results, it can be seen that the Pt-based catalyst modified with transition metal Fe has a higher yield in the selective hydrogenolysis of furfural or furfuryl alcohol to prepare 1,2-pentanediol, while the performance of Pt catalysts modified with other transition metals Co, Ni, Cu, Co, Ni, Cu, Ru, Pd, Rh catalysts modified with transition metal Fe and single metal Pt catalysts in catalyzing the selective hydrogenolysis of furfural to prepare 1,2-pentanediol is poor.

[0069] Example 6

[0070] The mass content of Fe was changed to 1.6%, and other conditions and processes were the same as those in Example 1. The catalytic results of the catalyst are shown in Table 2.

[0071] Example 7

[0072] The mass content of Fe was changed to 2.5%, and other conditions and processes were the same as those in Example 1. The catalytic results of the catalyst are shown in Table 2.

[0073] Example 8

[0074] The mass content of Fe was changed to 4.0%, and other conditions and processes were the same as those in Example 1. The catalytic results of the catalyst are shown in Table 2.

[0075] Example 9

[0076] The mass content of Pt was changed to 2.0%, and other conditions and processes were the same as those in Example 1. The catalytic results of the catalyst are shown in Table 2.

[0077] Example 10

[0078] The mass content of Pt was changed to 3.0%, and other conditions and processes were the same as those in Example 1. The catalytic results of the catalyst are shown in Table 2.

[0079] Embodiment 11

[0080] The mass content of Pt was changed to 4.0%, and other conditions and processes were the same as those in Example 1. The catalytic results of the catalyst are shown in Table 2.

[0081] Example 12

[0082] The mass content of Pt was changed to 2.0%, the mass content of Fe was changed to 1.6%, and other conditions and processes were the same as those in Example 1. The catalytic results of the catalysts are shown in Table 2.

[0083] Table 2 Effect of different Fe content or Pt content on catalytic activity

[0084]

[0085] *Others include small amounts of tetrahydrofurfuryl alcohol, cyclopentanone or 1,5-pentanediol, etc., and the overall material is conserved.

[0086] It can be seen from Table 2 that 1,2-pentanediol can be obtained with high selectivity when the mass contents of transition metals Fe and Pt are within the preferred range.

[0087] Example 13

[0088] The reaction temperature was changed to 150° C., and other conditions and processes were the same as those in Example 1. The catalytic results of the catalysts are shown in Table 3.

[0089] Embodiment 14

[0090] The reaction temperature was changed to 160° C., and other conditions and processes were the same as those in Example 1. The catalytic results of the catalysts are shown in Table 3.

[0091] Embodiment 15

[0092] The reaction pressure was changed to 2 MPa, and the other conditions and processes were the same as those in Example 1. The catalytic results of the catalysts are shown in Table 3.

[0093] Example 16

[0094] The reaction pressure was changed to 4 MPa, and the other conditions and processes were the same as those in Example 1. The catalytic results of the catalysts are shown in Table 3.

[0095] Embodiment 17

[0096] The mass concentration of the furfural aqueous solution was changed to 10%, and the other conditions and processes were the same as those in Example 1. The catalytic results of the catalyst are shown in Table 3.

[0097] Embodiment 18

[0098] The mass concentration of the furfural aqueous solution was changed to 20%, and the other conditions and processes were the same as those in Example 1. The catalytic results of the catalyst are shown in Table 3.

[0099] Embodiment 19

[0100] The mass concentration of the furfural aqueous solution was changed to 40%, and the other conditions and processes were the same as those in Example 1. The catalytic results of the catalyst are shown in Table 3.

[0101] Table 3 Effect of different reaction conditions on catalytic activity

[0102]

[0103] *Others include a small amount of tetrahydrofurfuryl alcohol, cyclopentanone or 1,5-pentanediol, etc., and the overall material conservation is maintained. As shown in Table 3: under the above reaction conditions, the selectivity of 1,2-pentanediol can still be maintained above 75%.

[0104] Example 20 Catalyst Circulation Test

[0105] 1Pt0.8Fe / MgTiO x Taking the catalyst as an example, 2g of catalyst was loaded into the fixed bed reactor, and hydrogen was controlled by a mass flow meter to flow from top to bottom through the catalyst bed. The reaction raw material was a 2wt% furfural aqueous solution, which was pumped into the catalyst bed from top to bottom through a high-performance liquid chromatography pump. The reaction temperature was 140°C, the hydrogen pressure was 1MPa, and the mass space velocity was 0.3h -1When the hydrogen flow rate was 30 mL / min, after 200 hours of stable operation, the selectivity of 1,2-pentanediol still remained above 75%.

Claims

1. An application of a catalyst in the hydrogenolysis of furfural or furfuryl alcohol to 1,2-pentanediol, characterized in that: In an intermittent stirred reactor or a continuous fixed bed, furfural and / or furfuryl alcohol are used as raw materials, water is used as solvent, and 1,2-pentanediol is prepared under the action of a Pt-based catalyst modified with transition metal Fe; The composition of the catalyst is Pt-Fe / MgMO x , 1≤x≤3, M is one or more of Zn, Ti, Mn, Al, Si, and the Mg content is in the carrier MgMO x The mass fraction is 15-60wt%, preferably 30-60wt%, more preferably 40-60wt%; the catalyst active component is Pt, and the loading amount of Pt is 0.1-10wt% of the carrier mass, preferably 0.4-4wt%, more preferably 1-2wt%; the catalyst promoter component is Fe, and the loading amount of Fe is 0.05-5wt% of the carrier mass, preferably 0.3-4wt%, more preferably 0.5-2wt%.

2. The use according to claim 1, characterized in that: The carrier is prepared by a sol-gel method or a coprecipitation method; the yield of the product 1,2-pentanediol is not less than 75%.

3. The use according to claims 1-2, characterized in that: The active component Pt and the auxiliary agent Fe were loaded on the carrier MgMO3 by impregnation method.

4. The use according to claim 3, characterized in that: In the impregnation process, the precursor raw material of Pt is one or more of platinum chloride, chloroplatinic acid, platinum nitrate, and platinum complexes (such as tetraammine dichloroplatinum, platinum acetylacetonate, bis(tri-tert-butylphosphine)platinum, dichloro(1,5-cyclooctadiene)platinum, etc.); the precursor raw material of Fe is one or more of ferric nitrate, ferric acetate, and ferric chloride.

5. The use according to any one of claims 1 to 4, characterized in that: The catalyst is used in the selective hydrogenolysis reaction of furfural or furfural alcohol. The reaction raw materials are furfural or furfural alcohol, the solvent is water, the mass concentration of furfural and / or furfural alcohol in water is 0.1-50%, the hydrogen pressure is 0.1-10MPa, the reaction temperature is 80-300°C, and the mass ratio of the catalyst to furfural or furfural alcohol is 0.1-5 (preferably 1-4).

6. The use according to claim 5, characterized in that: The mass concentration of furfural and / or furfuryl alcohol in water is preferably 1-30%, the hydrogen pressure is preferably 1-5 MPa, and the reaction temperature is preferably 120-160°C.

7. The use according to claim 1 or 5 or 6, characterized in that: The reaction time in the intermittent stirred reactor is 6-15h (preferably 8-12h); The space velocity in the continuous fixed bed is 0.01-5h -1 (Preferably 0.1-1h -1 ).

Citation Information

Patent Citations

  • Method for preparing 1,2-pentanediol by furfuryl alcohol liquid phase selectivity and hydrogenolysis

    CN104370702A

  • Application of composite oxide supported Pt catalyst in preparation of pentanediol from furfural

    CN113318735A